A Literature Review on Emotional Intelligence, Spiritual Intelligence, and Learning Interest from an Islamic Education Perspective - Achmad Defri Juliansyah; Salsabila Putri; Didit Darmawan (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to examine the relationship between emotional intelligence, spiritual intelligence, and learning interest from the perspective of Islamic education. The objective of this study is to synthesize existing literature and explore how emotional and spiritual dimensions contribute to fostering students' learning interest within the framework of Islamic educational values. This study employs a literature review method by examining and analyzing various books, journal articles, and academic publications related to emotional intelligence, spiritual intelligence, learning interest, and Islamic education. The findings indicate that emotional intelligence plays a significant role in helping students manage their emotions, develop positive social interactions, and maintain motivation throughout the learning process. Spiritual intelligence contributes to the development of life meaning, self-awareness, moral responsibility, and a stronger connection with religious values, which can enhance students’ engagement in learning activities. From the perspective of Islamic education, both forms of intelligence are closely associated with the cultivation of iman (faith), taqwa (piety), akhlaq (moral character), and self-discipline. The reviewed literature suggests that the integration of emotional and spiritual intelligence supports the development of stronger and more sustainable learning interest among students. The novelty of this study lies in its integrative approach that connects emotional intelligence, spiritual intelligence, and learning interest within the context of Islamic education. This review offers a more holistic perspective by emphasizing the interrelationship of emotional, spiritual, and educational values in shaping students’ learning interest and overall development.